Age- and Sex-Specific Reference Values for Media/Lumen Ratio in Small Arteries and Relationship With Risk Factors. Issue 6 (June 2018) - Bruno, Rosa Maria; Grassi, Guido; Seravalle, Gino; Savoia, Carmine; Rizzoni, Damiano; Virdis, Agostino
Abstract : Small-artery remodeling is an early feature of target organ damage in hypertension and retains a negative prognostic value. The aim of the study is to establish age- and sex-specific reference values for media/lumen in small arteries obtained in humans by biopsy. Data from 91 healthy individuals and 200 individuals with cardiovascular risk factors in primary prevention from 4 Italian centers were pooled. Sex-specific equations for media/lumen in the healthy subpopulation, with age as dependent variable, were calculated. These equations were used to calculate predicted media/lumen values in individuals with risk factors and Z scores. The association between classical risk factors and Z scores was then explored by multiple regression analysis. A second-degree polynomial equation model was chosen to obtain sex-specific equations for media/lumen, with age as dependent variable. In the population with risk factors (111 men, age 50.5±14.0 years, hypertension 80.5%), media/lumen Z scores were independently associated with body mass index (standardized β=0.293, P =0.0001), total cholesterol (β=0.191, P =0.031), current smoking (β=0.238, P =0.0005), fasting blood glucose (β=0.204, P =0.003), systolic blood pressure (β=0.233, P =0.023), and female sex (β=0.799, P =0.038). A significant interaction between female sex and total cholesterol was found (β=−0.979, P =0.014). Results were substantially similar in the hypertensive subgroup. A method to calculate individual values of remodeling and growth index based on reference values was also presented. Age- and sex-specific percentiles of media/lumen in a healthy population were estimated. In a predominantly hypertensive population, media/lumen Z scores were associated with major cardiovascular risk factors, including body mass index, cholesterol, smoking, glucose, and systolic blood pressure. Significant sex differences were observed. Abstract : Supplemental Digital Content is available in the text.